2018
DOI: 10.1093/jhps/hny023
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthroscopy as a treatment for obturator neuropathy secondary to intra-pelvic ganglion: a case report

Abstract: The most common types of cystic lesions around the hip joint are synovial or ganglion cysts. In rare cases, the cysts can compress adjacent structures and cause symptoms to arise. Obturator neuropathy secondary to a hip ganglion cyst is a rare phenomenon, with scarce reports on suggested treatment options. Hip arthroscopy is a potential minimally invasive treatment that has yet to be described in such cases. We present a 52-year-old male suffering from obturator neuropathy caused by an intra-pelvic ganglion cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In our review of the literature, we found that a protocol for intrapelvic access by arthroscopic means has not been previously published. Of note, Avnieli et al 9 described the removal of an intrapelvic obturator ganglion cyst by dilation and fluid decompression through the stalk using principles of 1-way valve destruction. It is unclear whether their approach consisted of instrumentation within the pelvis itself.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, we found that a protocol for intrapelvic access by arthroscopic means has not been previously published. Of note, Avnieli et al 9 described the removal of an intrapelvic obturator ganglion cyst by dilation and fluid decompression through the stalk using principles of 1-way valve destruction. It is unclear whether their approach consisted of instrumentation within the pelvis itself.…”
Section: Discussionmentioning
confidence: 99%
“…The articular branch was not readily visible on standard imaging, which could be related to fluid dynamics at the time of the exam, leading to relatively low cyst volume at the joint. For future cases where the joint connection is not apparent or easily identifiable on preoperative imaging, alternative modalities may be considered, like high-resolution ultrasound, [10][11][12] magnetic resonance arthrography, [13][14][15] or through 3D reconstruction. 16 Here, thinner slices on MRI or computed tomography may also be used by clinicians to better delineate the joint connection and plan operative intervention.…”
Section: Observationsmentioning
confidence: 99%